Network analyses reveal which symptoms improve (or not) following an Internet intervention (Deprexis) for depression. Issue 2 (11th November 2019) - Mullarkey, Michael C.; Stein, Aliza T.; Pearson, Rahel; Beevers, Christopher G.
Abstract: Background: Depression is a heterogeneous collection of symptoms. Prior meta‐analyses using symptom sum scores have shown the Internet intervention, Deprexis, to be an efficacious treatment for depression. However, no prior research has investigated how Deprexis (or any other Internet intervention for depression) impacts specific symptoms of depression. The current study utilizes symptom‐level analyses to examine which symptoms are directly, indirectly, or minimally influenced by treatment. Methods: Network analysis and mean‐level approaches examined which symptoms, assessed by the Quick Inventory of Depression Symptoms, were affected by an 8‐week course of Deprexis compared with a waitlist in a nationally recruited sample from the United States ( N  = 295). Results: Deprexis directly improved the symptoms of sadness and indecision . Changes in these symptoms, in turn, was associated with a change in early insomnia, middle insomnia, self‐dislike, fatigue, anhedonia, suicidality, slowness, and agitation . All of these symptoms (except for agitation and early insomnia ) show decreases with Deprexis compared with a waitlist after correcting for multiple comparisons. Six additional symptoms, particularly the somatic symptoms, were not impacted by Deprexis compared with a waitlist. Conclusions: In this sample, the efficacy of Deprexis was due to its direct impact on sadness and indecision . Examining the treatment‐related change in specific symptoms may facilitate a more nuanced understanding of how a treatment works compared with examining symptom sum scores. Symptom‐level approaches may also identify symptoms that do not improve and provide important direction for future treatment development.